2020
DOI: 10.1002/onco.13607
|View full text |Cite
|
Sign up to set email alerts
|

Wild-typeAPCIs Associated with Poor Survival in Metastatic Microsatellite Stable Colorectal Cancer

Abstract: Background. The prognostic implication of wild type APC (APC-WT) in microsatellite stable (MSS) metastatic colorectal cancer (mCRC) is not well defined. Methods. APC prognostic value was evaluated retrospectively in two independent cohorts of patient with MSS mCRC with a confirmatory analysis from a public data set from Memorial Sloan Kettering Cancer Center (MSKCC). Results. In comparison to the APC-mutant (APC-MT) population (n=255), APC-WT patients (n = 86) tended to be younger (59% of age <40 vs 26% of age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
13
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 32 publications
(47 reference statements)
4
13
0
1
Order By: Relevance
“…Colorectal (322, 33.6%) and thoracic (229, 23.9%) accounted for 57.5% of all cancer diagnosis in our cohort, and TP53, APC, KRAS, and LRP1B mutation rates are higher in colorectal cancers and non-small cell lung cancers (NSCLC) [ 26 , 27 , 28 , 29 ]. APC gene mutations are known to be associated with chromosomal instability, however, similar to our findings several studies have identified that mutated APC was associated with improved survival as compared to wild-type APC in colorectal cancer [ 30 , 31 , 32 , 33 , 34 ].…”
Section: Discussionsupporting
confidence: 88%
“…Colorectal (322, 33.6%) and thoracic (229, 23.9%) accounted for 57.5% of all cancer diagnosis in our cohort, and TP53, APC, KRAS, and LRP1B mutation rates are higher in colorectal cancers and non-small cell lung cancers (NSCLC) [ 26 , 27 , 28 , 29 ]. APC gene mutations are known to be associated with chromosomal instability, however, similar to our findings several studies have identified that mutated APC was associated with improved survival as compared to wild-type APC in colorectal cancer [ 30 , 31 , 32 , 33 , 34 ].…”
Section: Discussionsupporting
confidence: 88%
“…On top of that, the low number of patients in the RAS/PIK3CA mutated subgroups did not allow us to properly assess the interaction with the two treatment arms. Finally, in light of the poor prognostic role of APC wild-type status in mCRC, 26,27 we acknowledge that the low frequency of APC mutations in our dataset is clearly related to the relatively low coverage of the gene sequence by the hotspots included in this custom panel.…”
Section: Discussionmentioning
confidence: 97%
“…Однако при возникновении мутации он теряет способность связывать и разрушать β-катенин, в результате чего последний проникает в ядро и активирует транскрипцию ряда онкогенов, в том числе c-myc, циклин D1, которые являются промоторами клеточной пролиферации. Мутации в гене APC при спорадическом КРР встречаются довольно часто и могут составлять до 75 % случаев, мутации, как правило, возникают уже на ранней стадии развития опухоли [20,21]. Ген TP53, изменения в котором наряду с геном APC чаще всего встретились в обследованной группе, является наиболее известным опухолевым супрессором, отвечающим за стабильное состояние генома.…”
Section: материал и методыunclassified